Clinical Evaluation of Siemens SARS-CoV-2 Total Antibody assay and IgG assay using the Dimension EXL 200 in the Tokyo Metropolitan area. Issue 11 (November 2021) - Igawa, Gene; Yamamoto, Takamasa; Baba, Yuna; Shinozuka, Konomi; Yuri, Maiko; Wakita, Mitsuru; Misawa, Shigeki; Miida, Takashi; Ai, Tomohiko; Tabe, Yoko
Abstract: Background: We evaluated the efficacy of the Siemens SARS-CoV-2 Total Antibody assay (CV2T) and IgG assay (CV2G) that can detect antibodies against the receptor binding domain of S antigen in patients with COVID-19 in a Tokyo metropolitan area. Methods: Sensitivity and antibody levels were examined by CV2T and CV2G on Dimension EXL 200 using 236 serum samples obtained from 79 RT-PCR confirmed COVID-19 patients at multiple time points and were compared with disease severity by the World Health Organization criteria. The assay specificity was evaluated using samples collected before the COVID-19 pandemic. Results: The sensitivity of CV2T and CV2G were low (16.7–21.4%) in days 0–6 and increased to 43.8–52.5% in days 7–13 and to 80.8–90.0% in days 14–20. The seroprevalences persisted after day 21 to days past 42 regardless of disease severity. In every day grouping, mean antibody levels were higher in severe cases than in mild cases with a significant difference in days 14–20 and days 20–27. The specificity was 97.9 % (95% CI; 92.8–99.8) for CV2T and 99.0 % (95% CI; 94.6–100) for CV2G. Conclusions: Our results indicate a high specificity and high sensitivity at 14 days of CV2T and CV2G as antibody detection assays. Abstract : COVID-19, SARS-CoV-2, Serology, Antibody testing.